The Role of Risk Management and Business Control for a Small Business - Syaifuddin, Syaifuddin; A. Fedchenko, Elena; Thanh Nguyen, Phong; Laxmi Lydia, E.; Shankar, K. (Opción, 2019)
Now a days, economic environment is growing widely, so the risk man- agement become popular as compare to earlier year. The growth of any economy is always related to these small and medium size enterprises. Business management is most important factor in any type of business, as it relates to growth of business. Any business always comes with mul- tiple risk factors in market place. So risk management is important for maintaining balance of our business and there growth. Business risk can destroy small business, so the risk management is important to prevent business. In the paper, the risk management process is studied and business controls are introduced to prevent small and medium size company. It has given effective solution for business control in market- place. This paper proposed the role of risk management in corporation, internal and external risk management, and project risk and business control management process.